2023
DOI: 10.3389/pore.2023.1611123
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics of head and neck squamous cell cancer in young adults: A retrospective single-center study

Abstract: We aimed to characterize clinical and prognostical factors of primary head and neck squamous cell carcinoma (HNSCC) in 85 young patients (≤39 years, median age: 37 years; between 2000–2018) in comparison with 140 institutional general HNSCC patients (median age: 61.5 years). The patient’s medical records were collected from the institutional database. The prevalence of smoking and alcohol consumption (65.8% and 48.1%) in the young group exceeded the regional population average but was below the institutional (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
1
3
0
1
Order By: Relevance
“…This might originate either from defective cell cycle control or the dysfunctional clearance of malignant cells. In the latter scenario, tumor cells with a less aggressive phenotype might also survive, which might theoretically be in line with the more favorable survival data for young patients [6,7].…”
Section: Introductionsupporting
confidence: 56%
See 3 more Smart Citations
“…This might originate either from defective cell cycle control or the dysfunctional clearance of malignant cells. In the latter scenario, tumor cells with a less aggressive phenotype might also survive, which might theoretically be in line with the more favorable survival data for young patients [6,7].…”
Section: Introductionsupporting
confidence: 56%
“…Furthermore, the age distribution of young patients was heavily distorted towards the cut-off value of 39 years, and the oral cavity-the site with the most environmental exposure-was the most common location among the young but not the general patient population. Our pilot results suggested that young HNSCC patients might have greater vulnerability to various carcinogens [6]. This might originate either from defective cell cycle control or the dysfunctional clearance of malignant cells.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…Embora fatores de risco tradicionalmente associados (tabagismo e etilismo) estejam presentes nesses indivíduos, a duração da exposição não parece ser suficiente para o aumento do risco de câncer e, portanto, as causas para esse início precoce ainda não estão claras. 3 Mesmo com a redução da prevalência do tabagismo na maioria dos países de alta renda nos últimos 20 anos levando a um declínio na incidência do HNSCC, a infecção cancerígena pelo papilomavírus humano (HPV) emergiu como um importante fator de risco que tem levado a um aumento na incidência de câncer durante o mesmo período. 4,5 A relação entre a infecção por HPV, o surgimento de câncer na região de cabeça e pescoço e os mecanismos moleculares envolvidos têm se consolidado com o tempo.…”
Section: Introductionunclassified